Produksi Program Acara â€œPro 2 Activityâ€ di Pro 2 RRI Semarang (Pengarah Acara ) - Roli Harni Purba, Juita; Pradekso, Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Radio Republik Indonesia is the oldest radio station in Indonesia and is the only radio owned by the Indonesian government. As a public broadcasting institution, RRI has a vision of realizing an Indonesian public broadcasting institution as a trusted and worldwide radio. RRI has a very wide network, from Aceh to Papua. However, there are still many young people who donâ€™t know Radio Republik Indonesia. The number of private radios that have sprung up today causes the popularity of RRI decreased. In addition, the image of RRI as news radio and radio for parents in the society, so it is considered less attractive for young people who need entertainment and the latest things. In order to make RRI and its programs known to the public, especially young people, one solution that can be done is to re-concept or re-create the program